1999
DOI: 10.1103/physrevb.60.14585
|View full text |Cite
|
Sign up to set email alerts
|

Spin-fluctuation exchange study of superconductivity in two- and three-dimensional single-band Hubbard models

Abstract: In order to identify the most favorable situation for superconductivity in

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
68
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 34 publications
15
68
0
Order By: Relevance
“…Namely in this case, spin triplet pairing is expected to dominate strongly over singlet since ferromagnetic spin fluctuations arise for t ′ ∼ 0.5 and n ∼ 2 (or equivalently t ′ ∼ −0.5 and n ∼ 0) due to the large density of states at the Fermi level. This can be considered as well established because a number of approaches, including a FLEX study 31,48 , perturbational studies 49,50 , a T -matrix approximation 51 , and a renormalization group study 29 , reach (at least qualitatively) the same conclusion in this parameter regime. Since pairs may be formed at large distances for dilute career density, here we calculate the pairing interaction vertex also for the singlet sp3 channel shown in the inset of Fig.10(b).…”
Section: Near Full Fillingmentioning
confidence: 84%
“…Namely in this case, spin triplet pairing is expected to dominate strongly over singlet since ferromagnetic spin fluctuations arise for t ′ ∼ 0.5 and n ∼ 2 (or equivalently t ′ ∼ −0.5 and n ∼ 0) due to the large density of states at the Fermi level. This can be considered as well established because a number of approaches, including a FLEX study 31,48 , perturbational studies 49,50 , a T -matrix approximation 51 , and a renormalization group study 29 , reach (at least qualitatively) the same conclusion in this parameter regime. Since pairs may be formed at large distances for dilute career density, here we calculate the pairing interaction vertex also for the singlet sp3 channel shown in the inset of Fig.10(b).…”
Section: Near Full Fillingmentioning
confidence: 84%
“…One also gets the correct order of magnitude of the superconducting and superfluid transition temperature T c when the model parameters are inferred from experiments in the normal state of the above systems. For the case of a nearly half-filled single band, the calculations showed that the Eliashberg superconducting transition temperature T c is higher for the tetragonal (quasi-2D) than cubic (3D) lattice [3][4][5][6]. Particularly striking is the comparison between the cubic antiferromagnetic metal CeIn 3 and the closely related compound CeCoIn 5 [7].…”
Section: Introductionmentioning
confidence: 98%
“…Scalapino et al have shown, with the random phase approximation, that d x 2 −y 2 pairing gives way to d xy in a three-dimensional cubic lattice when charge fluctuations become large with the introduction of the off-site interaction. 4 However, systematic studies are yet to come for the charge fluctuations, in contrast to the spin-fluctuation mediated superconductivity for which favorable situations for its occurrence has been extensively discussed 5,6 .…”
Section: Introductionmentioning
confidence: 99%